High-efficiency adsorption of Cd2+ and Cr3+ by sodium vanadate nanowire arrays - Peng, Dengzeyu; Fan, Xin; Fang, Dong (Frontiers in Materials, 2023)
We sincerely thank the editor and the reviewer for their valuable feedback that we have used to improve the quality of our manuscript. For more accurate expression, we have modified the sodium vanadate in the title and part of the text to sodium vanadate nanowire arrays.The reviewers' comments and point-to-point response are laid out as follows.1. The novelty of the work should be established.Response: We thank the reviewer for pointing this out and we have revised. In this work, the prepared Na5V12O32 nanowire arrays was found to be nanostructured with a relatively high specific surface area and a high adsorption capacity compared to the same type of adsorbent. At the same time, there are no relevant reports on the adsorption of Cd 2+ and Cr 3+ , which broadens the of Na5V12O32 nanowire arrays in this field of heavy metal ion removal.